2020
DOI: 10.1177/1756284820959225
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis: age-related malignancy detection rates at upper gastrointestinal endoscopy

Abstract: Background: Age is an important and objective risk factor for upper gastrointestinal (GI) malignancy. The accuracy of various age limits to detect upper GI malignancy is unclear. Determination of this accuracy may aid in the decision to refer symptomatic patients for upper GI endoscopy. The aim of this analysis was to synthesize data on upper GI malignancy detection rates for various age limits worldwide through meta-analysis. Methods: We searched MEDLINE, EMBASE, and Web of Science in November 2018. Selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 49 publications
1
12
1
Order By: Relevance
“…A recent systematic review showed that the YoE values for the detection of gastric and esophageal cancer were reported separately in several original studies [ 9 ]. However, as the overlap of upper gastrointestinal symptoms is very frequent in real-life practice [ 17 ], the YoE for all types of UGIM should be considered together.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent systematic review showed that the YoE values for the detection of gastric and esophageal cancer were reported separately in several original studies [ 9 ]. However, as the overlap of upper gastrointestinal symptoms is very frequent in real-life practice [ 17 ], the YoE for all types of UGIM should be considered together.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the overlap of upper gastrointestinal symptoms is very frequent in real-life practice [ 17 ], the YoE for all types of UGIM should be considered together. In the abovementioned systematic review, apart from studies in Africa which generally showed that esophageal cancer was the most predominant UGIM and gastric cancer accounted for less than half of all UGIMs, almost all large-scale studies in the West and in Asia consistently showed that gastric cancer accounted for more than two-thirds and up to 80% of all UGIM cases [ 9 ]. Duodenal cancer was very rare and only reported in a few large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations